Impact of Adoption and Application of PMBOK® Guide on Project Performance in Kenya’s Construction Industry: A Multivariate Analysis - Mwanjama Katani, Erastus; Ntarangui Ng’Olua, Thomas (Multidisciplinary Journal of Technical University of Mombasa, 2025)
The construction industry in Kenya continues to face persistent performance challenges, including delays, cost overruns, and quality shortfalls. These issues have been partly attributed to inconsistent project management practices and limited adoption of structured frameworks. This study investigates the relationship between the application of the Project Management Body of Knowledge (PMBOK®) Guide and project performance outcomes in the Kenyan construction industry. Drawing on data collected from 172 construction professionals, the study evaluates how varying levels of PMBOK® adoption affect four key dimensions of project performance: adherence to time, cost control, quality delivery, and stakeholder satisfaction. The analysis employs Multivariate Analysis of Variance (MANOVA) and Spearman’s rank correlation to examine whether deeper integration of PMBOK® processes is statistically associated with improved project outcomes. The findings reveal that higher levels of PMBOK® Guide application (especially partial to full adoption) correlate significantly with improvements in time management, quality assurance, and stakeholder satisfaction. Customized adoption, though less common, demonstrated the strongest performance association. However, cost control showed a weaker statistical linkage, suggesting the influence of external factors beyond PM process standardization. The study contributes to project management literature by offering empirical evidence from a developing country context, reinforcing the performance-enhancing potential of structured methodologies when appropriately adapted. It recommends institutionalizing PMBOK®-based training, aligning regulatory frameworks with standard practices, and fostering a culture of continuous project evaluation.
Keywords: PMBOK® Guide, Project performance, Construction industry, Process adoption, Kenya